2019
DOI: 10.1186/s12935-019-0860-8
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Mst1 overexpression combined with Yap knockdown augments thyroid carcinoma apoptosis via promoting MIEF1-related mitochondrial fission and activating the JNK pathway

Abstract: Background Cancer cell viability is strongly modulated by the Hippo pathway, which includes mammalian STE20-like protein kinase 1 (Mst1) and yes-associated protein (Yap). Although the roles of Mst1 and Yap in thyroid carcinoma cell death have been fully addressed, no study has determined whether differential modification of Mst1 and Yap could further suppress thyroid carcinoma progression. The aim of our study was to explore the antiapoptotic effects exerted by combined Mst1 overexpression and Yap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 61 publications
1
10
0
Order By: Relevance
“…Mitochondria function as a cellular powerhouse to provide a constant supply of ATP for performing numerous biological processes such as metabolism, proliferation, growth, metastasis, differentiation, angiogenesis, and apoptosis [ 1 ]. Their involvement in the development and progression of thyroid carcinoma is evident from the fact that mitochondrial proteins serve as potential targets of chemotherapeutic receptor tyrosine kinase inhibitor drugs such as vandetanib and cabozantinib [ 2 , 3 ]. Moreover, the inhibition of mitochondrial function via disruption of oxidative phosphorylation has been shown to enhance the response to chemotherapy [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mitochondria function as a cellular powerhouse to provide a constant supply of ATP for performing numerous biological processes such as metabolism, proliferation, growth, metastasis, differentiation, angiogenesis, and apoptosis [ 1 ]. Their involvement in the development and progression of thyroid carcinoma is evident from the fact that mitochondrial proteins serve as potential targets of chemotherapeutic receptor tyrosine kinase inhibitor drugs such as vandetanib and cabozantinib [ 2 , 3 ]. Moreover, the inhibition of mitochondrial function via disruption of oxidative phosphorylation has been shown to enhance the response to chemotherapy [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mitochondrial dysfunction is reported to be associated with cancer cell death ( 19 ). To investigate whether FOXG1 was involved in the regulation of NPC mitochondrial function, the copy number of mtDNA was detected via RT-qPCR.…”
Section: Resultsmentioning
confidence: 99%
“…Changes in the structure and function of mitochondria in tumor cells lead to an increase in the absorption and utilization of glutamine, thereby meeting the bioenergy requirements of tumor cells, which is known as tumor mitochondrial metabolic reprogramming ( 17 ). Accumulating evidence has revealed that mitochondria serve an important role in cancer metabolism, proliferation, apoptosis and metastasis ( 18 , 19 ). However, the specific regulatory relationship between FOXG1 and NPC progression remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…At the molecular level, Sirt3 inactivated the Mst1-JNK pathway and thus suppressed the expression of SRV2, a novel mediator of mitochondrial fission. The Mst1-JNK axis is known to control mitochondrial fission in liver cancer [43], hyperglycemia-induced vascular dysfunction [44], thyroid carcinoma [45], breast cancer [46], acute cardiac stress [47], and colorectal cancer [48]. In addition, SRV2 induces mitochondrial fission by promoting F-actin polymerization [49, 50].…”
Section: Discussionmentioning
confidence: 99%